Perancangan Sistem Informasi Media Pembelajaran Pada Taman Kanak-Kanak Kali Bening Berbasis Web - Muklas Adi Putra; Suendri; Indah Ananda (Bulletin of Computer Science Research, 2022)
In learning activities, sometimes students easily get bored with an explanation from a teacher. Including young children who still have a sense of wanting to play, manual or formal learning will certainly make children easily bored. Therefore the author aims to change the way of learning by introducing web-based learning. To motivate children's creativity by learning to use existing technological innovations. So that children are not too bored in learning in class every day (except holidays). The author makes direct observations of objects, to find out what learning methods are applied in Kali Bening Kindergarten. Using a web-based application designed using a programming language and MySQL as a database server.